2016
DOI: 10.1002/14651858.cd008870.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Aminosalicylates for induction of remission or response in Crohn's disease

Abstract: Analysis 8.2. Comparison 8 Mesalamine (4-4.5 g/day) versus budesonide, Outcome 2 Adverse events.. .. .. Analysis 8.3. Comparison Mesalamine (4-4.5 g/day) versus budesonide, Outcome 3 Serious adverse events.. . Analysis 8.4. Comparison 8 Mesalamine (4-4.5 g/day) versus budesonide, Outcome 4 Withdrawal due to adverse events. Analysis 9.1. Comparison 9 Mesalamine versus sulfasalazine (alone or in combination with corticosteroids), Outcome 1 Induction of remission (CDAI < 150

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 103 publications
2
117
1
5
Order By: Relevance
“…5 Aminosalicylates (5 ASAs) are important anti inflammatory drugs that are frequently used for anti inflammatory therapy in patients with ulcerative colitis 3 . By contrast, 5 ASA based drugs show little or no efficacy in inducing res olution of clinical symptoms and tissue inflammation in patients with Crohn's disease 4 .…”
mentioning
confidence: 99%
“…5 Aminosalicylates (5 ASAs) are important anti inflammatory drugs that are frequently used for anti inflammatory therapy in patients with ulcerative colitis 3 . By contrast, 5 ASA based drugs show little or no efficacy in inducing res olution of clinical symptoms and tissue inflammation in patients with Crohn's disease 4 .…”
mentioning
confidence: 99%
“…22 However a recent metaanalysis has reaffirmed that 5-ASA has little benefit for the treatment of active CD. 20 In concordance with this evidence the actual treatment guideline for pediatric CD recommends oral 5-ASA only for selected patients with a very mild colonic disease. 1 Only 13% of CD patients in our cohort had colonic-only disease at diagnosis, whereas nearly half of all CD patients received oral 5-ASA at some time point.…”
Section: -Asa In CDmentioning
confidence: 83%
“…20 Furthermore nearly half of the CD patients in our cohort were treated with oral 5-ASA during their disease course. Earlier pediatric studies which suggested a possible benefit of 5-ASA in the treatment of small intestinal CD 21 may have influenced these prescribing practices.…”
Section: -Asa In CDmentioning
confidence: 99%
“…High-dose mesalamine (3 to 4.5 g/day) was not superior to placebo for induction of remission (RR 2.02; 95 % CI 0.75 to 5.45) or response (n=615). At the same time, no statistically significant difference was found between high-dose mesalamine and conventional corticosteroids (RR 1.04; 95 % CI 0.79 to 1.36; n=178) [67]. Another meta-analysis came up with slightly different conclusions.…”
mentioning
confidence: 91%